2016
DOI: 10.4236/ijcm.2016.72016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Risk of Malnutrition in Elderly Hypertensive Patients with or without Associated Cardiovascular Risk Factors Living at Home (West Algeria) Sidi-Bel-Abbès

Abstract: Undernutrition is frequently underestimated in the elderly, because clinical manifestations are non-specific. For the francophone Club geriatrics and nutrition, poly medication is one of the warning signs to be the possibility of malnutrition in an elderly person. To do this, it is particularly interesting to verify what the profiles of hypertensive patients who are at risk of malnutrition are. This component remains very little explored and studies are lacking. The authors conducted a descriptive cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Our study reported that older adults with peripheral vascular disease, asthma, and hypertension had a significant risk of malnutrition. We also found that 55% of older Saudis were malnourished and diagnosed with hypertension, whereas studies in Algeria ( 60 ) and Bangladesh ( 19 ) reported that 39.8 and 88.9% of older people, respectively, were malnourished and diagnosed with hypertension. On the other hand, our study showed that 19.8% of the participants who were at risk of malnutrition had been diagnosed with asthma or chronic lung disease, significantly less than that reported in Bangladesh (79%) ( 19 ).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Our study reported that older adults with peripheral vascular disease, asthma, and hypertension had a significant risk of malnutrition. We also found that 55% of older Saudis were malnourished and diagnosed with hypertension, whereas studies in Algeria ( 60 ) and Bangladesh ( 19 ) reported that 39.8 and 88.9% of older people, respectively, were malnourished and diagnosed with hypertension. On the other hand, our study showed that 19.8% of the participants who were at risk of malnutrition had been diagnosed with asthma or chronic lung disease, significantly less than that reported in Bangladesh (79%) ( 19 ).…”
Section: Discussionmentioning
confidence: 42%
“…However, appetite and nutrient requirements remain the same or increase, which can further lead to weight gain during this age period ( 58 ). The frequency of obesity, which is associated with several chronic diseases, such as diabetes, hypertension, and cardiovascular disease, increases in older people aged between 60 and 70 years, particularly in women ( 59 , 60 ). A high percentage of our study participants were obese (38.7%) and overweight (36.2%), and obesity was more prevalent in women (45.9%) than in men (31.9%), while more men were overweight (41.3%) than were women (30.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Operational Definitions: Height: distance from the ground to the highest point of standing person. Weight: measured with a minimum of clothing using an electronic scale (34). BMI Body mass index (BMI) which is weight in kg/ height in m2 index used to calculate nutritional status of an individual 35 .…”
Section: Introductionmentioning
confidence: 99%